2015
DOI: 10.1002/anie.201510132
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Borylative Opening of Propargyl Cyclopropane, Epoxide, Aziridine, and Oxetane Substrates: Ligand Controlled Synthesis of Allenyl Boronates and Alkenyl Diboronates

Abstract: A new copper‐catalyzed reaction for the stereo‐ and regioselective synthesis of alkenyl diboronates and allenyl boronates is presented. In this process propargyl derivatives of strained three/four‐membered rings were employed as substrates and B2pin2 was used as the boronate source. Selective formation of the alkenyl diboronate versus the allenyl boronate products was controlled by the choice of phosphine ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…11,12 To the best of our knowledge, there is no extant catalytic protocol for preparation of enantiomerically enriched trisubstituted allenyl boronates (i.e., α -addition to furnish vi , Scheme 1b). 13 An attractive way to synthesize trisubstituted allenyl boronates ( viii , Scheme 2a) enantioselectively would be by 1,3-enyne hydroboration, 14 which might proceed via Cu–allenyl species vii . We wished to investigate whether, despite the relative robustness of a Cu–allenyl bond (vs the formerly studied Cu–alkyl bonds 3g ), there might be cases where the stereochemical integrity of a Cu–allenyl intermediate might be jeopardized, and whether conditions may be modified for achieving high enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 To the best of our knowledge, there is no extant catalytic protocol for preparation of enantiomerically enriched trisubstituted allenyl boronates (i.e., α -addition to furnish vi , Scheme 1b). 13 An attractive way to synthesize trisubstituted allenyl boronates ( viii , Scheme 2a) enantioselectively would be by 1,3-enyne hydroboration, 14 which might proceed via Cu–allenyl species vii . We wished to investigate whether, despite the relative robustness of a Cu–allenyl bond (vs the formerly studied Cu–alkyl bonds 3g ), there might be cases where the stereochemical integrity of a Cu–allenyl intermediate might be jeopardized, and whether conditions may be modified for achieving high enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Four major components were identified by 1 H NMR spectroscopy in the reaction mixture being unreacted starting material S1 (12 %), diborylated 1,4‐diene 1 (15 %), α‐hydroxyallene 17 (45 %) and the monoborylated allene 41 (≈28 %, cf. α‐borylation of the alkyne unit; for details, see the Supporting Information) [16] . These data illustrate that an excess of B 2 pin 2 was required to favor the formation of the diborylated diene, and that the monoborylated allene 41 is a likely precursor to 1 .…”
Section: Resultsmentioning
confidence: 77%
“…a-borylation of the alkyne unit;f or details,s ee the Supporting Information). [16] These data illustrate that an excess of B 2 pin 2 was required to favor the formation of the diborylated diene,a nd that the monoborylated allene 41 is al ikely precursor to 1.I nt he absence of as ufficiently large excess of B 2 pin 2 alternative parasitic pathways could be favored. Thef ormation of a-hydroxyallene 17 as the major compound under these reaction conditions suggested that alcohol-promoted protodeborylation of 41 is competitive.…”
Section: Angewandte Chemiementioning
confidence: 81%
“…Szabò reported copper‐catalyzed borylative ring openings of three‐ and four‐membered rings bearing an adjacent triple bond [77] . The reaction afforded allenylboronates using less basic and hindered phosphines, such as tri‐1‐naphthylphosphine.…”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%